Evaluation of hs-CRP in Type 2 Diabetes Mellitus and its Relationship with Glycemic Control and Disease Complications - Ouda, Ghsin Al-ban Adnan; Rasheed, Suaad Mohammed H. (Medical Science Journal for Advance Research, 2024)
Background: Type 2 diabetes mellitus is the predominant kind of condition characterized by impaired insulin production. It is linked to a disturbance in the metabolism of lipids, proteins, and carbohydrates. Aim of the study: The present study try to explore the role of inflammation process in type 2 diabetes mellitus (T2DM) through assessment the level of High Sensitivity-CRP (hs- CRP). Subject and Methods: The study is a case-control study conclude 78 randomly selected patients with mean age 60.44 ± 11.18 years old and they had a documented medical records of T2DM, they invited to participation in the study when they attended to The Specialist Centre for diseases of Endocrine and Diabetes in Babylon for medical checkup. The healthy control group consists of 57 randomly selected non diabetic volunteers, with mean age 57.37 ± 9.16 years old, all of them had normal fasting blood glucose and normal HbA1c. Both diabetic and healthy control groups were matched in regard to age and sex and other demographic characters while there is difference between them in regard family history for diabetes as well as in RBS & HbA1c. Serum levels of hs-CRP were measured by ELISA technique. Results: The results showed that the mean serum concentrations of hs-CRP were significantly higher in diabetic patients than control, 0.93 ± 0.27 ng/ml in patients versus 0.36 ± 0.18 ng/ml in controls, respectively) with p< 0.001, the mean level of hs-CRP inpatients with poor glycemic control had approximately double the mean level of than those with good glycemic control, P=0.02. Conclusion: the high levels of hs-CRP among diabetes strength the inflammatory hypothesis that predispose to T2DM.